2019
DOI: 10.1111/tbj.13302
|View full text |Cite
|
Sign up to set email alerts
|

Is Ductography Still Warranted in the 21st century?

Abstract: Objective To determine the utility of ductography in conjunction with mammography and ultrasound in patients with pathologic nipple discharge, and the incremental role of MRI after triple‐modality evaluation. Materials and Methods We retrospectively reviewed the medical records of patients who had presented with pathologic nipple discharge and had undergone mammography and/or ultrasound and ductography between January 1, 2005, and October 31, 2010. We tested the diagnostic sensitivity, specificity and accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…ACR guidelines recommend mammography or digital breast tomosynthesis as the initial examination for women aged ≥ 40 years [ 7 ]. Positive mammography findings in patients with PND include microcalcifications, mass lesions, architectural distortion, asymmetry, and/or solitary dilated ducts [ 21 27 28 ]. The benefits of additionally performing ductography for mammography-positive patients remain unclear, although several reports have shown various rates of correlation (80.0% [4/5]–33.4% [2/6]) between ductography and mammography findings for malignant lesions [ 21 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACR guidelines recommend mammography or digital breast tomosynthesis as the initial examination for women aged ≥ 40 years [ 7 ]. Positive mammography findings in patients with PND include microcalcifications, mass lesions, architectural distortion, asymmetry, and/or solitary dilated ducts [ 21 27 28 ]. The benefits of additionally performing ductography for mammography-positive patients remain unclear, although several reports have shown various rates of correlation (80.0% [4/5]–33.4% [2/6]) between ductography and mammography findings for malignant lesions [ 21 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Positive mammography findings in patients with PND include microcalcifications, mass lesions, architectural distortion, asymmetry, and/or solitary dilated ducts [ 21 27 28 ]. The benefits of additionally performing ductography for mammography-positive patients remain unclear, although several reports have shown various rates of correlation (80.0% [4/5]–33.4% [2/6]) between ductography and mammography findings for malignant lesions [ 21 27 ]. Moreover, ductography has been shown to facilitate preoperative localization of the causative lesion in 36% (13/36) of the cases [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ductography might have self-limiting minor complications (such as duct per-Open Journal of Radiology foration and extravasation of the contrast material) [3]. The technical failure is considered to be a limitation.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, the most common cause of nipple discharge is benign diseases such as intraductal lesion. However, PND can also be the first sign of underlying malignancy (in a small percentage, with an incidence varying in literature from 5% to 23%) [2] [3].…”
Section: Introductionmentioning
confidence: 99%
“…Galactography is an X-ray examination that uses mammography and an iodinated contrast to obtain imaging of the inside of the duct to evaluate lesions causing nipple discharge. Recent studies have shown that galactography helps in precisely locating masses within breast tissue and provides useful information for the surgical approach and planning [9].…”
Section: Introductionmentioning
confidence: 99%